Electrocatalytic hydrodehalogenation of atrazine in aqueous solution by Cu@Pd/Ti catalyst. (April 2015) - Chen, Ya-Li; Xiong, Lu; Song, Xiang-Ning; Wang, Wei-Kang; Huang, Yu-Xi; Yu, Han-Qing
Graphical abstract: Highlights: Uniformly dispersed Pd nanoparticles on Cu sphere cores were obtained. The existence of Cu core substantially increased the EASA of Pd. The Cu@Pd/Ti cathode exhibited a high activity and stability for the ECH of atrazine. Abstract: Electrocatalytic hydrodehalogenation is a cost-effective approach to degrade halogenated organic pollutants in groundwater, and Pd-based catalysts have been found to be an efficient cathode material for this purpose. In this work, a novel Cu@Pd bimetallic catalyst loaded on Ti plate was prepared via combined electrodeposition and galvanic replacement for electrocatalytic hydrodehalogenation of atrazine, a typical halogenated pollutant. The obtained bimetallic catalyst with uniformly dispersed Pd nanoparticles possessed a large electrochemically active surface area of 572 cm 2 . The Cu@Pd/Ti cathode exhibited a higher electrocatalytic efficiency towards atrazine reduction than the individual Pd/Ti or Cu/Ti cathodes, and achieved up to 91.5% within 120 min under a current density of 1 mA cm −2 . Such an electrocatalytic reduction followed pseudo-first-order kinetics with a rate constant of 0.0214 min −1 . Atrazine was selectively transformed to dechlorinated atrazine, and its degradation pathway was identified. Current density was found to have a critical influence on the atrazine reduction due to the competitive hydrogen evolution reaction at a higher current density. The fabricated bimetallic catalyst also exhibited a good stability. This work provides an efficient and stable electrocatalyst for chlorinated contaminate removal and groundwater remediation.